Loranthus micranthusLinn.: Biological Activities and Phytochemistry - Zorofchian Moghadamtousi, Soheil; Hajrezaei, Maryam; Kadir, Habsah Abdul; Zandi, Keivan (Hindawi, 2013)
Loranthus micranthus Linn. is a medicinal plant from the Loranthaceae family commonly known as an eastern Nigeria species of the African mistletoe and is widely used in folkloric medicine to cure various ailments and diseases. It is semiparasitic plant because of growing on various host trees and shrubs and absorbing mineral nutrition and water from respective host. Hence, the phytochemicals and biological activities of L. micranthus demonstrated strong host and harvesting period dependency. The leaves have been proved to possess immunomodulatory, antidiabetic, antimicrobial, antihypertensive, antioxidant, antidiarrhoeal, and hypolipidemic activities. This review summarizes the information and findings concerning the current knowledge on the biological activities, pharmacological properties, toxicity, and chemical constituents of Loranthus micranthus. © 2013 Soheil Zorofchian Moghadamtousi et al.